Proceeding #1 Dakar 5-19/05/2002. - Audéoud, Fabienne; Calvert, Sheena; Golding, Johnny; Hamet Bâ, Pierre; Ikwe-Tyehimba, Ajamu; Leisdovich, Sarah; Loontjens, Jannah; Maike Mei Lan; Muller, Nat; Tacq, Filiep; Zakravsky, Katherina; de Boeck, Lieven (Maastricht : Jan Van Eyck Akademie Maastricht, 2003)
Konrad, Aglaia ; Maike Mei Lan ; Czerepok, Hubert ; Ikwe-Tyehimba, Ajamu ; Klaschka, Ella ; Abdulla, Mohamed ; Castillo Deball, Mariana ; Tacq, Filiep ; de Boeck, Lieven ; Simkus, Mindaugas ; Martins, Andreia ; Almeida, Charly d' ; Zinkpe, Dominique ; Sakho, Moussa ; Dieng, Modou ; Lô, Ndary ; Bouabdellah, Zoulikha
Engels
Frans
Nederlands
boek